The Dissemination of Pineapple Processed Innovations as a Form of Peatland Restoration for the Bunga Desa Group in Selingsing, Pelintung Village, Riau - Zuhri, Moh Sayful; Rusdiyana, Eksa; Rahayu, Rahayu (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2022)
Low fertility on peatlands has its own impact on people living in peatland areas. Areas that have peatlands include Selingsing village, Pelintung, Dumai City, Riau Province. In addition to influencing environmental factors, this also affects factors in the economy. Therefore, it is necessary to seek a solution for revitalization in order to overcome the problems in peatlands. One of the revitalization activities is an activity that has economic value but does not damage the environment. There needs to be socialization related to the use of peatlands and supporting innovations. Pineapple is one of the plants that can live well on peatlands. It is hoped that innovation in pineapple processing can be a solution for revitalizing peatlands. There are so many innovations of processed pineapple that can be of high economic value. The community service program that is packaged through real work lecture activities and the collaboration with the Peat Restoration Agency can provide benefits in the program. Through this program, he hopes to be able to provide the role of academics in devoting themselves to the community, especially in peatlands